2014
DOI: 10.1038/tpj.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

A combined high CYP2D6-CYP2C19 metabolic capacity is associated with the severity of suicide attempt as measured by objective circumstances

Abstract: This study examined, for the first time, whether a high CYP2D6-CYP2C19 metabolic capacity combination increases the likelihood of suicidal intent severity in a large study cohort. Survivors of a suicide attempt (n=587; 86.8% women) were genotyped for CYP2C19 (*2, *17) and CYP2D6 (*3, *4, *4xN, *5, *6, *10, wtxN) genetic variation and evaluated with the Beck Suicide Intent Scale (SIS). Patients with a high CYP2D6-CYP2C19 metabolic capacity showed an increased risk for a severe suicide attempt (P<0.01) as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…A recent study by Llerena and collaborators examining suicide risk among subjects having both high CYP2D6 and CYP2C19 expression is interesting [24]. Thus, patients with a high CYP2D6-CYP2C19 metabolic capacity showed an increased risk for a severe suicide attempt as measured future science group Expression of CYP2C19 & CYP2D6 in the developing & adult human brain: variability in cognition, risk for depression & suicide Editorial by the SIS-objective circumstance subscale, particularly in absence of a family history of suicide.…”
Section: Synergy Of Increased Cyp2c19 and Cyp2d6 Activitymentioning
confidence: 91%
“…A recent study by Llerena and collaborators examining suicide risk among subjects having both high CYP2D6 and CYP2C19 expression is interesting [24]. Thus, patients with a high CYP2D6-CYP2C19 metabolic capacity showed an increased risk for a severe suicide attempt as measured future science group Expression of CYP2C19 & CYP2D6 in the developing & adult human brain: variability in cognition, risk for depression & suicide Editorial by the SIS-objective circumstance subscale, particularly in absence of a family history of suicide.…”
Section: Synergy Of Increased Cyp2c19 and Cyp2d6 Activitymentioning
confidence: 91%
“…Taken together, these findings suggest that the role of CYP2C19 on depressive symptoms appears to be complex and might be different according to specific ADs, also in light of the fact that combinations of variants located in genes coding for different CYP enzymes, such as CYP2D6 (Penas-Lledo et al, 2015), might also be relevant to explain part of the variability in AD therapy outcome.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast with these results, a recent study found that patients undergoing treatment with escitalopram carrying the CYP2C19*17 allele were more likely to switch to another antidepressant within one year of follow‐up (Jukic, Haslemo, Molden, & Ingelman‐Sundberg, ). Taken together, these findings suggest that the role of CYP2C19 on depressive symptoms appears to be complex and might be different according to specific ADs, also in light of the fact that combinations of variants located in genes coding for different CYP enzymes, such as CYP2D6 (Penas‐Lledo et al, ), might also be relevant to explain part of the variability in AD therapy outcome.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, since drugs and plants are metabolized by a myriad of different enzymes that are encoded by their respective genes, substrate specificity and drug dosage seem to be only two of many factors [22] contributing to a drug response measured by quantitative variables such as degree of efficacy or number/severity of side effects. In support of that, despite the evidence about the relationship of CYP2D6 and drug response [6], the combined use of parallel alternate metabolic CYP pathways [23] that can compensate in the case of CYP2D6 PMs to individualize treatments with certain CYP2D6 sub- strates is, as yet, very limited, as is use of other genes such as those encoding drug receptors also involved in response [24]. Finally, individualized therapy to increase drug safety in different populations will also largely benefit from collecting and interrogating large genomics datasets in order to identify biological mechanisms associated with observed outcomes [25].…”
Section: Discussionmentioning
confidence: 94%